Studies on Antioxidant and Hepatoprotective Activities of Extracts and Active Fraction of Pachypodanthium staudtii (Annonaceae) Stem Bark: Activities of Fraction of Pachypodanthium staudtii (Biological Sciences - PJSIR, 2024)
This study evaluates the antioxidant and hepatoprotective activities of the stem bark extracts (methanol, PSM and dichloromethane, PSD) and active fraction of Pachypodanthium staudtii. In-vitro antioxidant activity was determined by DPPH, total phenolic content (TPC) and reducing power assay (RPA), while the hepatoprotective activity was verified against CCl4-induced acute hepatotoxicity in rats. Serum biomarkers (ALT, AST, ALP), in-vivo antioxidant (superoxide dismutase, SOD and catalase, CAT) and malondialdehyde (MDA) levels were estimated using standard models. Histopathological studies were carried out on the liver isolates. The result showed that PSM significantly inhibited DPPH (IC50=63.70µg/mL) compared to PSD (IC50=1591.58 µg/mL). PSM showed a higher phenolic content of 2536.26 mgGAE/g compared to 1916.78 mgGAE/g for PSD. Fraction A showed a phenolic content of 553.01 mgGAE/g. Significant (P